2020
DOI: 10.1016/j.breast.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complications according to incision types in nipple-sparing mastectomy and immediate reconstruction

Abstract: Background Nipple-sparing mastectomy (NSM), followed by immediate reconstruction (IR) of the breast, has become a preferred surgical procedure with good cosmesis results and patient satisfaction. However, nipple-areolar complex (NAC) ischemia and necrosis remain major problems after NSM and IR. Methods We retrospectively analyzed patients who underwent NSM and IR at Gangnam Severance Hospital from January 2009 to June 2018. We compared the patient characteristics and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…There are several studies confirming the inframammary fold incision as a safe and cosmetically perfect incisional access. 3 The visibility of the retroareolar region and the exact excision of the breast gland and the ducts is feasible in experienced hands after a certain learning curve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies confirming the inframammary fold incision as a safe and cosmetically perfect incisional access. 3 The visibility of the retroareolar region and the exact excision of the breast gland and the ducts is feasible in experienced hands after a certain learning curve.…”
mentioning
confidence: 99%
“…In general, we are the proponents and advocates for prepectoral implant based breast reconstruction after nipple-sparing mastectomy and promote the further implementation of this method 4 -but iBAG a milestone? Roland Reitsamer 1 Florentia Peintinger 2,3 Frederike Klaassen-Federspiel 1 Andreas Sir 1 1 Department of Senology, University Hospital Salzburg,…”
mentioning
confidence: 99%
“…To prove the safety of this procedure, it is necessary to compare the incidence of NAC necrosis in this procedure with that in the conventional superolateral oblique incision approach. In a recent study of 53 patients who underwent NSM via the conventional superolateral radial incision, Park et al [ 19 ] observed nipple necrosis in 9 (17.0%) patients. Further, Algaithy et al [ 20 ] reported a 16.2% incidence of NAC necrosis among 37 patients who received NSM via a superolateral incision.…”
Section: Discussionmentioning
confidence: 99%
“…Nipple-areolar complex (NAC) ischemia and necrosis are common complications after nipple-sparing mastectomy (NSM) with a prevalence range of 0–48%, mostly 10–15% [ 1 , 2 , 3 , 4 ]. Several risk factors for NAC-related complications after a mastectomy with breast reconstruction (BR) have been identified, including obesity, ptosis, large breast weight and volume, prior radiotherapy history, and incision type [ 1 , 5 , 6 , 7 , 8 ], among which, obesity is a well-known risk factor [ 9 , 10 , 11 ]. Obesity is evaluated using body mass index (BMI), which reflects only body height and weight but does not reflect body composition, such as muscle and adipose tissue compositions.…”
Section: Introductionmentioning
confidence: 99%